Revisiting the interpreter's role : a study of conference, court, and medical interpreters in Canada, Mexico, and the United States - Angelelli, Claudia (Benjamins translation library ;, 2004)
Through the development of a valid and reliable instrument, this book sets out to study the role that interpreters play in the various settings where they work, i.e. the courts, the hospitals, business meetings, international conferences, and schools. It presents interpreters' perceptions and beliefs about their work as well as statements of their behaviors about their practice. For the first time, the administration and results of a survey administered across languages in Canada, Mexico and the United States offer the reader a glimpse of the interpreters' views in their own words. It also dis.